Sonic Hedgehog Is a Determinant of γδ T-Cell Differentiation in the Thymus - Mengrelis, Konstantinos; Lau, Ching-In; Rowell, Jasmine; Solanki, Anisha; Norris, Sonia; Ross, Susan; Ono, Masahiro; Outram, Susan; Crompton, Tessa (Frontiers in Immunology, 2019)
Here we investigate the function of Hedgehog (Hh) signalling in thymic  T-cell maturation and subset differentiation. Analysis of Hh mutants showed that Hh signalling promotes  T-cell development in the thymus and influences  T-cell effector subset distribution. Hh-mediated transcription in thymic  cells increased  T-cell number, and promoted their maturation and increased the NKT subset, whereas inhibition of Hh-mediated transcription reduced the thymic  T-cell population and increased expression of many genes that are normally down-regulated during  T-cell maturation. These changes were also evident in spleen, where increased Hh signalling increased NKT cells, but reduced CD27-CD44+ and V2+ populations. Systemic in vivo pharmacological Smoothened-inhibition reduced T-celland NKT cells in the thymus, and also reduced splenic T-cell and NKT populations, indicating that Hh signalling also influences homeostasis of peripheral  T-cell populations. Taken together our data indicate that Sonic Hedgehog is an important determinant of  T-cell effector subset differentiation.